(untitled) (International Journal of Built Environment and Sustainability, 2021)
Throughout the historical process humans have shaped the environment that they lived in and developed it according to their needs. The living culture has been formed with various spatial setups in dwellings which are the most basic habitats of humankind. Today, functionality comes into prominence in this living culture which is referred to as traditional dwellings. This shows that the continuity is ensured by presenting mass and cultural harmony between spatial setups and the garden and neighboring dwelling relations. Amongst the traditional dwellings, Turkish house is also considered as an important example, which provides continuity with its diverse plan organizations and spatial characteristic. The courtyard character in traditional dwellings is the space that is effective in the organization of spatial which sheds light on present day with various parameters. This is because the dwelling is located in the courtyard. Moreover, the courtyard, which starts with the entrance and where the households carry out their daily lives, is very significant for the Turkish dwelling as it contains both natural and cultural characteristics. The traditional dwellings of the village of Islamköy, which is located in the Atabey district in Isparta province of Turkey, are discussed within the scope of the study, which examines how the concept of courtyard that contains the functional and aesthetic values of the Turkish dwelling, forms various plan organizations and spatial characters in many cultures, affects the spatial quality. Spatial quality parameters were examined on five second-degree registered traditional dwellings located on Okul Street in the Islamköy village. Three basic principles have been determined which are functional, aesthetic and ecological and the sub-parameters of these determined principles have been introduced with the information and documents obtained from the literature. The AHP method was used to determine the priorities of the parameters in this direction. Thus, taking into account the spatial quality parameters, the priority parameters of the courtyard character in the traditional dwellings of Islamköy were determined